2013
DOI: 10.1002/cmdc.201300093
|View full text |Cite
|
Sign up to set email alerts
|

E‐64c‐Hydrazide: A Lead Structure for the Development of Irreversible Cathepsin C Inhibitors

Abstract: Cathepsin C is a papain-like cysteine protease with dipeptidyl aminopeptidase activity that is thought to activate various granule-associated serine proteases. Its exopeptidase activity is structurally explained by the so-called exclusion domain, which blocks the active-site cleft beyond the S2 site and, with its Asp 1 residue, provides an anchoring point for the N terminus of peptide and protein substrates. Here, the hydrazide of (2S,3S)-trans-epoxysuccinyl-L-leucylamido-3-methylbutane (E-64c) (k2/Ki =140±5 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
(49 reference statements)
0
15
0
Order By: Relevance
“…These results strengthen the hypothesis that targeting DPPI might also be an interesting therapeutic approach for NSPs-mediated metabolic diseases. To date, only a few DPPI inhibitors have been described but they were not tested yet in an in-vivo model for NSPs mediated inflammatory diseases (Table 1) (6466).…”
Section: Therapeutic Approaches In Nafldmentioning
confidence: 99%
“…These results strengthen the hypothesis that targeting DPPI might also be an interesting therapeutic approach for NSPs-mediated metabolic diseases. To date, only a few DPPI inhibitors have been described but they were not tested yet in an in-vivo model for NSPs mediated inflammatory diseases (Table 1) (6466).…”
Section: Therapeutic Approaches In Nafldmentioning
confidence: 99%
“…demonstrated that similar epoxides are in fact capable of withstanding 95:5 v/v TFA/H2O. 112 So, we were confident that the global deprotection using TFA could be conducted on the full-length epoxide-containing peptide precursor 3.6. The on-resin cyclization strategy could be applied to the synthesis of CDA3a and CDA4a.…”
Section: Retrosynthetic Analysis Of Cda3a and Cda4amentioning
confidence: 89%
“…However, Radzey et al demonstrated that similar epoxides are, in fact, capable of withstanding 95:5 v/v TFA/H 2 O. 19 Keeping this in mind, we decided to adopt an on-resin cyclization strategy of a protected, lipidated peptide, similar to what we used for the total synthesis of daptomycin. 20 The synthesis began with the coupling of Fmoc-D-HOPhGly(OTBS)-OH to the α-NH 2 group of resin-bound dipeptide 12 (Scheme 6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an anchoring point for the N terminus of peptide substrates is provided by the Asp‐1 residue. In this context, Schaschke's group [145] reported a series of (2 S ,3 S )‐oxirane‐2,3‐dicarboxylic acid hydrazides 88 (Scheme 16) as inhibitors for cathepsin C. For selectivity studies, a set of Boc protected alkylhydrazines was synthesized and the target compounds were obtained through solution coupling of E‐64c with hydrazines, in presence of TBTU/DIEA, followed by Boc deprotection (Scheme 16). E‐64 hydrazide ( l ‐31 ‐hydrazide) was recognized as a lead compound for development of irreversible cathepsin C inhibitors.…”
Section: Synthesis Of Epoxysuccinates‐based Chemical Probesmentioning
confidence: 99%